'It's like, instant respect': Coworking spaces as identity anchoring environments in the new economy. (19th July 2022) - Bacevice, Peter A.; Spreitzer, Gretchen M.
Abstract: As employment relationships become more tenuous, as work grows increasingly virtual and as professional reputations circulate across online platforms, coworking provides individuals across various work arrangements with shared workspaces oriented towards sociability, visibility and convenience. Our study explores how coworking spaces also enable individuals to shape their professional identities while providing other important attributes of work to help it feel embodied and grounded. Drawing from interviews and surveys of members of a large coworking chain across the United States, we find that coworking spaces serve as identity anchoring environments . We find that many workers use material elements of the space to ground their professional identities in three ways: evidencing professional credibility, enacting a common ethos and energising connections with others. More broadly, we also find that coworking operators package and sell the physical, spatial and symbolic aspects of work to help certain workers signal their professional selves.